Effects of educational intervention based on childbirth scenarios on fear of childbirth in primiparous women - Farnaz Shaliha; Fatemeh Jafarzadeh-Kenarsari; Zahra Bostani-Khalesi; Saman Maroufizadeh; Zainab Alimoradi (Wolters Kluwer Medknow Publications, 2024)
BACKGROUND: Fear of childbirth (FOC) is one of the common reasons for choosing cesarean delivery without medical indications. The present study aimed to assess the effect of childbirth scenario-based educational intervention on FOC in primiparous women. MATERIALS AND METHODS: This study was conducted on 72 primiparous women attending comprehensive health care centers in Qazvin, Iran, in 2021. Participants were randomly placed in the control group (n = 38) and the intervention group (n = 34). The participants in the intervention group read the booklet of childbirth scenarios once a week for eight weeks. Data were collected using the demographic-fertility questionnaire and the Wijma Delivery Expectancy/Experience Questionnaire (W-DEQ) before the intervention, eight weeks after the intervention, and the first week after delivery. Data analysis was carried out using independent t-test, Chi-square, Fisher's exact, repeated measures analysis of variance (ANOVA), and analysis of covariance (ANCOVA). RESULTS: By controlling the FOC scores before the intervention, the mean total FOC scores eight weeks after the intervention and in the first week after delivery in the intervention group were significantly 34 units (95% CI: 27.3-40.7) and 22.9 units (95% CI: 14.6-31.1) lower than the control group respectively (P < 0.001). CONCLUSION: Based on the results, childbirth scenario-based intervention can effectively reduce FOC among primiparous women. Healthcare providers, especially midwives, can benefit from applying childbirth scenario-based intervention in prenatal care to reduce the FOC of pregnant women.